PERAN WAKAF DALAM PENDANAAN PENDIDIKAN DI ERA GLOBALISASI - Irwan Rusniawan; Hadi Nurhadi; Obar Subarja; Aprilliantoni (STKIP Subang, 2025)
This study examines the strategic role of waqf as an alternative and sustainable financing mechanism for education in the era of globalization. The increasing need for quality education and the limited capacity of conventional funding sources, such as government budgets and community contributions, require innovative models of financing. Waqf, as an Islamic social financial instrument with a long historical contribution to education, offers great potential to support the development of educational infrastructure, scholarship distribution, operational sustainability, and scientific research. This research employs a qualitative approach using a literature review design that analyzes scholarly articles, books, institutional reports, and regulatory documents related to waqf and educational funding. The findings indicate that waqf has historically acted as a backbone for educational development during the Islamic Golden Age and remains relevant today through modern forms such as cash waqf, waqf sukuk, and digital waqf platforms. However, challenges such as low waqf literacy, weak managerial capacity of nazir, and limited transparency hinder optimal utilization. The study concludes that optimizing waqf for educational financing requires strengthening governance, digital innovation, regulatory support, and increased public literacy. Waqf, if professionally managed and technologically integrated, can serve as a sustainable financial pillar for accessible, equitable, and high-quality education in the global era. Keywords: Waqf, Education Funding, Globalization, Islamic Social Finance, Cash Waqf;